Growth performance of Nellore Sheep and Aseel Poultry under Duplex Model Housing system in Scarce Rainfall Zone of Andhra Pradesh (Indian Journal of Animal Production and Management, 2025)
Small ruminants plays an important role in rainfed agriculture. Rearing of ram lambs  for fattening is a common practice in scarce rainfall zone of Andhra Pradesh. The  usual method of rearing is extensive system and provision of night shelter with mud  floor. Elevated floor system has many advantages to eliminate the existing problem  of ammonia accumulation in the shed and suitable for intensive feeding which also  reduces the cost on labour. Rearing of poultry and ram lambs under one shelter with  a concept of two-layer livestock system was developed at KVK, Yagantipalle. The  present study was conducted to assess the growth performance of ram lambs and  Aseel poultry under different systems. Higher body weight gain of Ram lambs and  poultry was observed under two-layer system compared to traditional system.
Keywords: Duplex model housing; Nellore sheep; Aseel and Growth performance